INCREASING WRITING SKILL OF NARRATIVE THROUGH DIRECTLY LEARNING MODELS STUDENT CLASS VII SMP 26 SAROLANGUN - Fahmi, Muhibul; Atmazaki, Atmazaki (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
This research aims at improving the students’ ability to convert an interview text into narrative text. Based on the facts, the students’ ability to convert interview text into narrative was still very low, due to the lack of students’ interest in learning. Besides, teaching method used by the teacher could not cultivate students' interest in learning especially in writing narrative. This research used direct instructional model. The subjects were students at SMP 26 Sarolangun in the academic year which consisted of 18 students. Data obtained in the form of qualitative data which were collected through observation and field notes. Quantitative data obtained through performance tests and questionnaire of students’ responses towards the learning. From the data obtained, it was found that direct instructional model could improve the students’ narrative writing skill. In addition, direct instructional model has created a situation that is more attractive, comfortable, and happier for the students.